First waikavirus infectious clones and vascular expression of green fluorescent protein from maize chlorotic dwarf virus - Stewart, Lucy R.; Willie, Kristen; Xie, Wenshuang; Todd, Jane; Tran, Hong Hanh (Frontiers in Virology, 2023)
Plant viruses classified in the genus Waikavirus, family Secoviridae, are positive sense single-stranded RNA viruses that include important pathogens of maize (maize chlorotic dwarf virus; MCDV) and rice (rice tungro spherical virus; RTSV). Many aspects of the molecular biology of waikaviruses remain unexplored because of experimental challenges and lack of infectious clones for low titer, phloem-limited, and obligately vector-transmitted waikaviruses. Here we report the first development of waikavirus infectious clones for two MCDV strains, MCDV-S and MCDV-M1, and insect-free launching of infections from these clones in maize by vascular puncture inoculation. We further developed a green fluorescent protein (GFP)-tagged MCDV clone by replacing the viral p27-encoding sequence with GFP-encoding sequence. GFP-tagged virus moved systemically in plants and caused symptomatic infection similar to wild type virus, with vascular expression of GFP. Development of waikavirus infectious clones is a major advance for this group of agriculturally significant viruses.